SCHWARTZ-MATSUO SYNDROME : AN IMPORTANT CAUSE OF SECONDARY GLAUCOMA : RARE CASE: Poster Presentation - Case Report - Resident - Fidalia; Perkasa, Teguh Ridho; Sari, Prima Maya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Schwartz-Matsuo syndrome is a rare ocular condition characterized by rhegmatogenous retinal detachment, elevated intraocular pressure, and open anterior chamber angle with presence of aqueous cells. The prevalence of Schwartz-Matsuo syndrome is quite low and only reported through case studies. Case Illustration : A 63 years old female complained a visual aquity was no light perception on the left eye (LE) since 2 months ago. The symptoms are gradually getting worse, history of ocular trauma, recent surgery, photopsia, peripheral visual field loss were denied. Patient came to the hospital with IOP elevation on left eye. On Gonioscopy we interpretated as open angle chamber and USG examination we founded retinal detachment, Anti-glaucoma medication were given but no success to lower the IOP. Discussion : Typically, retinal detachment is associated with low IOP. In Schwartz-Matsuo syndrome the opposite is observed with elevated IOP. Hypothesized that photoreceptor outer segments pass through the retinal break allows for fluid and photoreceptor outer segments to gain access, enter the anterior chamber and block aqueous outflow at the level of the trabecular meshwork. A significant increase in IOP can lead to visual loss and blindness complicated by glaucoma requiring further medical or surgical intervention. Referred to this patient, she came with IOP elevation, open angle anterior chamber and retinal detachment that clinically diagnosed as Schwartz-Matsuo syndrome. Conclusion : Schwartz-Matsuo syndrome is primarily a clinical diagnosis; Early detection of disease and prompt management of increased IOP and retinal detachment is essential for a good outcome.